Relevant incidental findings at abdominal multi-detector contrast-enhanced computed tomography: A collateral screening? - Sconfienza, Luca Maria (World J Radiol, 2015)
AIM: To investigate the prevalence of relevant incidental findings (RIFs) detected during routine abdominal contrast-enhanced computed tomography (CeCT). METHODS: We retrospectively evaluated the reports of a consecutive series of abdominal CeCT studies performed between January and May 2013. For each report, patients’ age and sex, admission as inpatient or outpatient, clinical suspicion as indicated by the requesting physician, availability of a previous abdominal examination, and name of the reporting radiologist were recorded. Based on the clinical suspicion, the presence and features of any RIFs (if needing additional workup) was noted. RESULTS: One thousand forty abdominal CeCT were performed in 949 patients (528 males, mean age 66 ± 14 years). No significant difference was found between inpatients and outpatients age and sex distribution (P > 0.472). RIFs were found in 195/1040 (18.8%) CeCT [inpatients = 108/470 (23.0%); outpatients = 87/570 (15.2%); P = 0.002]. RIFs were found in 30/440 (6.8%) CeCT with a previous exam and in 165/600 (27.5%) without a previous exam (P < 0.001). Radiologists’ distribution between inpatients or outpatients was significantly different (P < 0.001). RIFs prevalence increased with aging, except for a peak in 40-49 year group. Most involved organs were kidneys, gallbladder, and lungs. CONCLUSION: A RIF is detected in 1/5 patients undergoing abdominal CeCT. Risk of overdiagnosis should be taken into account.